Naples and tourism: conflicts of a dream realised? Analysis of a fast-changing urban landscape - Stefano De Falco; Alberto Corbino (AIMS Geosciences, 2023)
Urban landscape and tourism, a complementary binomial or a dual antithesis? The question is becoming more and more interesting, and it is a cause of concern among local administrators. To this end, we aim to investigate the dynamics of a specific case, the city of Naples (Italy), where the fast, increasing touristification of the historic city center - a phenomenon for which the expression "overtourism" is increasingly used – is now showing the other side of the coin. Through an interpretivist-constructivist epistemological approach based on the analysis of the context, the critical issues relating to an uncontrolled management of urban space are first brought to light and then some strategies and public policies that could prove effective in containing the phenomenon are proposed. Finally, the results found for the specific case of Naples are described in inductive terms to be replicable in similar contexts.